Genotype x environmental interaction on seed cotton yield and yield components - Mudada, Nhamo; Chitamba, James; Macheke, Tinotenda Obriel; Manjeru, Pepukai (Open Access Library, 2020)
Cotton yield and fibre quality parameters are dependent on the environment in which the crop is grown. A major challenge in crop genotype recommendations is genotype × environment interaction. The identification of cultivars with high adaptability and stability is one of the best ways to address this challenge. Genotype × Environmental interaction on Gosypium hirsutum was investigated. Ten genotypes were planted in a randomised complete block design with three replications. Collected data were subjected to Analysis of Variance (ANOVA) with genotype and location as factors. Additive Main Effect and Multiplicative Interaction model which combines standard analysis of variance with principal component analysis was used to investigate the genotype main effects, environment main effects and the GE interactions. Significant genotype × environment interactions existed for lint yield, boll weights, staple length, and fuzzy seed grade. There were no significant cultivar × site interactions on total seed cotton yield. Cotton cultivars respond differently to different growing conditions implying that, correct choice of varieties by growers for specific production conditions, must be a must to avoid losses due to genotype × environment interactions.